The Survival Condition and Immunoregulatory Function of Adipose Stromal Vascular Fraction (SVF) in the Early Stage of Nonvascularized Adipose Transplantation - Dong, Ziqing (Public Library of Science, 2013)
INTRODUCTION: Adipose tissue transplantation is one of the standard procedures for soft-tissue augmentation, reconstruction, and rejuvenation. However, it is unknown as to how the graft survives after transplantation. We thus seek out to investigate the roles of different cellular components in the survival of graft. MATERIALS & METHODS: The ratios of stromal vascular fraction (SVF) cellular components from human adipose tissue were evaluated using flow cytometry. Human liposuction aspirates that were either mixed with marked SVF cells or PBS were transplanted into nude mice. The graft was harvested and stained on days 1,4,7 and 14. The inflammation level of both SVF group and Fat-only group were also evaluated. RESULTS: Flow cytometric analysis showed SVF cells mainly contained blood-derived cells, adipose-derived stromal cells (ASCs), and endothelial cells. Our study revealed that most cells are susceptible to death after transplantation, although CD34+ ASCs can remain viable for 14 days. Notably, we found that ASCs migrated to the peripheral edge of the graft. Moreover, the RT-PCR and the immuno-fluorescence examination revealed that although the SVF did not reduce the number of infiltrating immune cells (macrophages) in the transplant, it does have an immunoregulatory function of up-regulating the expression of CD163 and CD206 and down-regulating that of IL-1β, IL-6. CONCLUSIONS: Our study suggests that the survival of adipose tissue after nonvascularized adipose transplantation may be due to the ASCs in SVF cells. Additionally, the immunoregulatory function of SVF cells may be indirectly contributing to the remolding of adipose transplant, which may lead to SVF-enriched adipose transplantation.